CHINESE LEGAL TERMINOLOGY IN THE FIELD OF PROPERTY LAW - KOZANECKA, Paulina (Comparative Legilinguistics, 2016)
This paper focuses on legal terminology related to the right of ownership in Poland and China. Legal translation concerning this language pair becomes increasingly necessary, considering numerous trade relations between these countries. Therefore doing the research on the terminology of property law in Poland and China is essential, and the right of ownership is the core of this branch of law in both examined countries. The aim of this paper is to present basic terms related to ownership: ownership rights, subjects and objects, as well as protection of the right of ownership depending on ownership type. The method of comparison of comparable texts was applied, and Chinese and Polish Constitution, Chinese General Principles of Civil Law, Chinese Property Law and Polish Civil Code were used as the research material.